Medium-term ionospheric response to the solar and geomagnetic conditions at low-latitude stations of the East African sector. Issue 1 (31st December 2023) - Woldemariam, Shumet; Gogie, Tsegaye
Abstract: In this study, we used GPS-TEC measurements from six stations in East Africa located in low/equatorial latitudes to investigate medium-term ionospheric response to solar and geomagnetic circumstances during 2014–2016. Daily mean solar proxies (F10.7 and SSN) and geomagnetic activity indices (Kp and Dst) were used to determine solar and geomagnetic activity effects on ionospheric vertical Total-Electron-Content (vTEC). We have applied statistical analysis and quadratic fits with solar indices to find the type of trends, forecast vTEC, and describe the daily fluctuations of vTEC. Asab and Debark had the highest vTEC values among the six stations during the months of equinoxes in which they are located at 13.06 0 and 13 0 geographic latitudes, respectively. The highest vTEC values were 86, 80, and 75 TECU in March, October, and April 2014, respectively; 72 TECU in March and April 2015, and 70 TECU in February 2015. Within 24 hours, the magnitudes of vTEC were greater in February, March, and April 2014, 2015, and 2016 than in the remaining months. The changes in vTEC have demonstrated good agreement with the trend of solar parameters, and F10.7 has a stronger correlation with vTEC than SSN by 20%. The effects of solar activity on GPS-vTEC were positive, whereas the vTEC was disturbed during the storm's main and recovery phases, which led to positive and negative ionospheric effects, respectively. We found both linear and non-linear trends. Nevertheless, when we approximated ( F 10.7) 2 and ( SSN ) 2 coefficients, linear trends in vTEC were dominant. The anticipated and observed vTEC measurements are in moderately good agreement.